2020
DOI: 10.3390/cells9091992
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Comparison between Sézary Syndrome and Lymphocytic-Variant Hypereosinophilic Syndrome Refines Biomarkers for Sézary Syndrome

Abstract: Sézary syndrome (SS), an aggressive cutaneous T-cell lymphoma (CTCL) with poor prognosis, is characterized by the clinical hallmarks of circulating malignant T cells, erythroderma and lymphadenopathy. However, highly variable clinical skin manifestations and similarities with benign mimickers can lead to significant diagnostic delay and inappropriate therapy that can lead to disease progression and mortality. SS has been the focus of numerous transcriptomic-profiling studies to identify sensitive and specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 143 publications
(260 reference statements)
1
5
0
Order By: Relevance
“…Sézary cell markers were consistent with previous studies (Fig. 2a) 2729 . We next analyzed pretreatment samples to identify the genes differentially expressed within Sézary cells between responding and non-responding patients (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Sézary cell markers were consistent with previous studies (Fig. 2a) 2729 . We next analyzed pretreatment samples to identify the genes differentially expressed within Sézary cells between responding and non-responding patients (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Immune analysis of the skin in SS shows a Th2 cytokine profile [10] and the malignant T cells exhibit a Th2 cytokine pattern with increased IL-4 [11]. From gene profiling studies, a unique gene expression phenotype of SS has been uncovered [12]. Gene expression changes in SS, such as decreased expression of IFN-γ, and increased expression of unique biomarker genes identified in SS such as TWIST1, and TOX are frequent and represent important features of CTCL [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of engrafted Sezary cells demonstrated that skin-resident CD4 + cells (clusters 2 and 5) clustered separately from the main spleen-resident CD4 + cell populations (clusters 0 and 1), suggesting tissue-specific regulation of gene expression programs. Genes highly expressed in clusters 2 and 4, including DUSP2 , NR4A2 , LMNA , FOS , SLC2A3 , and DUSP4 , were previously reported to be associated with Sezary leukemic cells ( Borcherding et al, 2019 ; Moerman-Herzog et al, 2020 ). Genes highly expressed in cluster 5 ( STMN1 , MKI67 ) are associated with cell proliferation.…”
Section: Resultsmentioning
confidence: 98%